PERANAN ADAT DALAM MELINDUNGI KELESTARIAN IMBO LAGHANGAN (HUTAN LARANGAN) PADA MASYARAKAT ADAT KENEGERIAN RUMBIO KABUPATEN KAMPAR PROVINSI RIAU - Elfiandri Elfiandri; Zulfan Saam; Thamrin Thamrin; W.E Tinambunan (Program Pascasarjana Universitas Riau, 2014)
The purpose of this research is to find out how the role of Customs in protecting theSustainability Imbo Laghangan (Forest) On Indigenous people of the land rumbio inthe District of Kampar in Riau Province.While that will be the focus of problems in thisresearch is how the role of Customs in protecting the Sustainability Imbo Laghangan(Forest) On Indigenous people of the land rumbio in the District of Kampar in RiauProvince. The location of this research is in the land rumbio in the District of Kamparin Riau Province. This research was conducted in more than six months. The object ofthis research is Indigenous people of the land rumbio in the District of Kampar in RiauProvince.The technique of collecting data is the technique of observation, interview anddocumentation. Technique to determine the source of data is by snowball Technique.The validity of data the study is done with the methods data triangulation at betweendata sources. The main data sources this study was a customary namely ninik mamak(the head tribes). While the complementary data source i.e., Elder Ward, clergy,ingeniously clever. The Methods of data analysis used is qualitative descriptive methodfor ethics and emic.